Aluminum alloy anodic oxidation treatment process
By using a solution of oxalic acid and glycolic acid in the aluminum alloy anodization treatment process for anodization treatment and carrying out hydration sealing treatment, the problem of insufficient wear resistance and corrosion resistance of aluminum alloy materials in the prior art is solved, and the microhardness, wear resistance and insulation performance of the material is significantly improved, which is suitable for the high-stable material needs in the semiconductor field.
Patent Information
- Application Number
- CN202411874081.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-07
AI Technical Summary
The existing aluminum alloy anodizing process has shortcomings in wear resistance and corrosion resistance, especially in applications in semiconductor fields, where the stability and wear resistance of the material are difficult to meet the high requirements.
A new aluminum alloy anodization treatment process is adopted, and a dense oxide film is formed by anodizing treatment using a solution of 20-40g/L oxalic acid and 4-6g/L glycolic acid, and hydration sealing treatment in water or water vapor at 98-105°C.
The microhardness, wear resistance and insulation properties of aluminum alloy materials have been significantly improved. Especially with the addition of glycolic acid, the wear resistance and insulation stability of the material have been significantly improved, extending the service life of the material and broadening its application fields.
Smart Images

Figure FT_1 
Figure FT_2
Abstract
Description
Technical Field
[0001] The invention relates to an aluminum alloy anodizing process, and in particular to a method for preparing a wear-resistant and highly stable aluminum alloy used in the semiconductor field. Background Art
[0002] Aluminum alloy is an alloy with Al as the main element. Other elements usually added are Zn, Cu, Mg, Mn, Si, Sn, etc. According to different processing methods, aluminum alloys can be divided into cast aluminum alloys and forged aluminum alloys. The most significant property of aluminum alloys is light weight. The density of Al is only 2.7g / cm 3 , which is only about 1 / 3 of steel. Therefore, aluminum alloys are widely used in industrial fields such as aerospace and automobile industries that are extremely in need of weight reduction. In addition, some aluminum alloys have high strength, exceeding structural steel, and high-strength aluminum alloys are also widely used in the construction industry. Aluminum alloys generally have excellent electrical and thermal conductivity, and transmission cables and electric heaters using aluminum alloys take advantage of this property. Aluminum is non-magnetic, which makes aluminum alloys also have important application value in the electrical and electronic industries. In addition, the non-toxicity and beautiful appearance of aluminum alloys make aluminum alloys often appear in daily necessities and decorations. The plasticity and easy processing of aluminum alloys allow aluminum alloys to be easily made into parts of various shapes, which greatly broadens the application range of aluminum alloys.
[0003] The main anodizing processes at present are: (1) Sulfuric acid anodizing (SAA) is a widely used anodizing process in industrial production because of its advantages such as low production cost, simple operation and less environmental pollution. The oxide film formed by sulfuric acid anodizing is generally colorless and transparent, with good hardness and wear resistance, and the film is easy to color, but its corrosion resistance is poor. Studies have shown that there are many holes and cracks of uneven sizes on the surface of sulfuric acid anodizing films, and its film quality and corrosion resistance are poorer than other anodizing films. (2) Chromic acid anodizing (CAA) Chromic acid anodizing is an anodizing treatment method widely used in the aircraft manufacturing industry. The oxide film is generally milky gray to dark gray. The film is relatively thin and soft, with low porosity (difficult to color), and its corrosion resistance is better than that of sulfuric acid anodizing film, but its wear resistance is poor. Liu's research found that the chromic acid anodizing film has few surface defects and has good corrosion resistance and fatigue resistance. However, because Cr6+ is highly toxic, it has gradually been replaced by other relatively environmentally friendly anodizing processes due to environmental issues. (3) Oxalic acid anodizing (OAA) Oxalic acid anodizing is also an anodizing technology widely used in the production process. Because oxalic acid is a weak acid, the dissolution rate of the oxide film is low during the film formation process, so it is easier to obtain an anodized film with low porosity, high hardness, good corrosion resistance, wear resistance and insulation properties. Studies have shown that oxalic acid anodizing of aluminum alloys can produce a fine and uniform porous oxide film, which confirms that the oxalic acid anodized film has a good protective effect on the substrate. (4) Phosphoric acid anodizing (PAA) Phosphoric acid anodizing is one of the earliest anodizing processes used for aluminum profiles. The anodized film formed by it is usually thin and has a high porosity. It is very suitable for use as a pretreatment step for bonding, spraying, etc., forming a layer on the surface of the aluminum profile with good adhesion and a certain conductivity. The bottom layer. However, due to its thin film layer and high porosity, its corrosion resistance is poorer than that of anodized films formed by other component electrolytes. (5) Mixed acid anodization: In order to expand the temperature range of the anodizing process and improve the efficiency of the anodized film formation, and obtain a film with better performance, as early as the last century, researchers considered using an anodizing process that mixed two or more acids as electrolytes to prepare anodized films. The electrolytes for mixed acid anodizing known to date are mainly based on acidic solutions such as sulfuric acid, oxalic acid and sulfonic acid, with appropriate additions of organic acids such as boric acid, oxalic acid and tartaric acid to form a mixed solution, such as boric acid-sulfuric acid type, oxalic acid-sulfuric acid type and tartaric acid-sulfuric acid. For example, when sulfuric acid-oxalic acid is used as the electrolyte of the mixed acid system, the anodized film formed by it often appears silvery white, has the characteristics of fast growth rate, high hardness, wear resistance and corrosion resistance, and can form a more uniform and dense film with excellent corrosion resistance than a single sulfuric acid system. Summary of the invention
[0004] Based on the above cognition, the present invention provides an aluminum alloy anodizing treatment process. The aluminum alloy anodizing prepared by the present invention is used in the processing field of insulating and wear-resistant semiconductor aluminum alloy materials. Through anodizing and sealing treatment, a dense oxide film is formed on the aluminum alloy substrate. The obtained aluminum alloy material has good microhardness, wear resistance and insulation properties. In particular, glycolic acid significantly improves the wear resistance and stability of the aluminum alloy substrate, broadens the service life and field of aluminum and aluminum alloys, and has broad application prospects in the fields of aerospace, electronics, semiconductors, and electrical.
[0005] Specifically: an aluminum alloy anodizing process comprises the following steps: (1) Using aluminum alloy as the substrate, the surface of the substrate is polished with sandpaper and then soaked in an alkaline solution; (2) Wash with water, dry with cold air, and activate with acid solution; (3) Wash with water and blow dry with cold air; (4) Anodizing treatment; (5) Hydration and sealing treatment; (6) Wash with water and blow dry with cold air; The solution used in the anodizing treatment is composed of 20-40 g / L oxalic acid, 4-6 g / L glycolic acid and deionized water; The power supply for anodizing is a DC power supply, and the aluminum alloy is immersed in the anodizing solution as the anode, the voltage is 40-50V, and the temperature is 5-10℃.
[0006] The hydration sealing is to seal the holes in water or water vapor at 98-105°C for 2-3 hours.
[0007] Sandpaper polishing uses 400#, 600#, 800#, 1000#, 1200#, and 1500# SiC sandpaper in sequence.
[0008] The alkaline solution is a 4.5-5.5wt.% NaOH aqueous solution, the alkaline washing time is 8-10min, the alkaline washing temperature is 25-30°C, and the alkaline washing method is immersion.
[0009] The acid solution is a 30 vol.% nitric acid aqueous solution, the pickling activation time is 20-30s, the pickling activation temperature is 25-30°C, and the pickling activation method is immersion.
[0010] The water washing method is flushing, and the time is 1.5-2 minutes.
[0011] Beneficial technical effect: The present invention discovers for the first time that glycolic acid has a very high effect on improving the hardness of the anodized film, as well as the wear resistance and insulation stability. The possible reason is that glycolic acid, as an organic acid, has good adsorption and complexing effects, which improves the integrity and corrosion resistance of the film layer. The possible reason for the improved stability is that glycolic acid can significantly reduce the fine cracks in the anodized film. The presence of fine cracks will cause significant fluctuations in the insulation parameters of the material, ultimately improving the stability of the material. On the premise of improved stability, the application of aluminum alloys in the semiconductor field is significantly expanded. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Attached Figure 1 Statistical results of wear resistance parameters of Example 1 of the present invention and Comparative Example 1.
[0013] Attached Figure 2 Statistical results of insulation parameters of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION Example 1
[0014] An aluminum alloy anodizing process is prepared by the following steps: (1) Aluminum alloy is used as the substrate, and the surface of the substrate is polished with sandpaper, and then immersed in an alkaline solution: the sandpaper polishing is performed using 400#, 600#, 800#, 1000#, 1200#, and 1500# SiC sandpaper in sequence.
[0015] The alkaline solution is a 5wt.% NaOH aqueous solution, the alkaline washing time is 9 minutes, the alkaline washing temperature is 27.5°C, and the alkaline washing method is immersion.
[0016] (2) Wash with water, blow dry with cold air, and activate with acid solution: the acid solution is 30 vol.% nitric acid aqueous solution, the pickling activation time is 25 s, the pickling activation temperature is 27 °C, and the pickling activation method is immersion.
[0017] (3) Wash with water and blow dry with cold air.
[0018] (4) Anodizing treatment: The solution used for anodizing treatment consists of 30 g / L oxalic acid, 5.3 g / L glycolic acid and deionized water. The power supply for anodizing is a DC power supply. The aluminum alloy is used as an anode and immersed in the anodizing solution. The voltage is 45 V and the temperature is 6 °C.
[0019] (5) Hydration and sealing treatment: Seal the holes in deionized water at 100°C for 2-3 hours.
[0020] (6) Wash with water and blow dry with cold air.
[0021] Comparative Example 1, a highly wear-resistant aluminum alloy coating material is prepared by the following steps: (1) Aluminum alloy is used as the substrate, and the surface of the substrate is polished with sandpaper, and then immersed in an alkaline solution: the sandpaper polishing is performed using 400#, 600#, 800#, 1000#, 1200#, and 1500# SiC sandpaper in sequence.
[0022] The alkaline solution is a 5wt.% NaOH aqueous solution, the alkaline washing time is 9 minutes, the alkaline washing temperature is 27.5°C, and the alkaline washing method is immersion.
[0023] (2) Wash with water, blow dry with cold air, and activate with acid solution: the acid solution is 30 vol.% nitric acid aqueous solution, the pickling activation time is 25 s, the pickling activation temperature is 27 °C, and the pickling activation method is immersion.
[0024] (3) Wash with water and blow dry with cold air.
[0025] (4) Anodizing treatment: The solution used for anodizing treatment is composed of 30 g / L oxalic acid and deionized water. The power supply for anodizing is a DC power supply. The aluminum alloy is used as an anode and immersed in the anodizing solution. The voltage is 45 V and the temperature is 6 °C.
[0026] (5) Hydration and sealing treatment: Seal the holes in deionized water at 100°C for 2-3 hours.
[0027] (6) Wash with water and blow dry with cold air. Example 2
[0028] An aluminum alloy anodizing process, characterized by comprising the following steps: (1) Using aluminum alloy as the substrate, the surface of the substrate is polished with sandpaper and then soaked in an alkaline solution; (2) Wash with water, dry with cold air, and activate with acid solution; (3) Wash with water and blow dry with cold air; (4) Anodizing treatment; (5) Hydration and sealing treatment; (6) Wash with water and blow dry with cold air; The solution used in the anodizing treatment is composed of 20 g / L oxalic acid, 4 g / L glycolic acid and deionized water; The power supply for anodizing is a DC power supply, and the aluminum alloy is immersed in the anodizing solution as the anode, with a voltage of 40V and a temperature of 5°C; The hydration sealing is to seal the pores in water or water vapor at 98°C for 2 hours.
[0029] Sandpaper polishing uses 400#, 600#, 800#, 1000#, 1200#, and 1500# SiC sandpaper in sequence.
[0030] The alkaline solution is a 4.5wt.% NaOH aqueous solution, the alkaline washing time is 8 minutes, the alkaline washing temperature is 25°C, and the alkaline washing method is immersion.
[0031] The acid solution is a 30 vol.% nitric acid aqueous solution, the pickling activation time is 20 s, the pickling activation temperature is 25° C., and the pickling activation method is immersion.
[0032] The washing method is flushing, and the time is 1.5 minutes. Example 3
[0033] An aluminum alloy anodizing process, characterized by comprising the following steps: (1) Using aluminum alloy as the substrate, the surface of the substrate is polished with sandpaper and then soaked in an alkaline solution; (2) Wash with water, dry with cold air, and activate with acid solution; (3) Wash with water and blow dry with cold air; (4) Anodizing treatment; (5) Hydration and sealing treatment; (6) Wash with water and blow dry with cold air; The solution used in the anodizing treatment is composed of 40 g / L oxalic acid, 6 g / L glycolic acid and deionized water; The power supply for anodizing is a DC power supply, and the aluminum alloy is immersed in the anodizing solution as the anode, with a voltage of 50V and a temperature of 10°C; The hydration sealing is to seal the holes in water or water vapor at 98-105°C for 3 hours.
[0034] Sandpaper polishing uses 400#, 600#, 800#, 1000#, 1200#, and 1500# SiC sandpaper in sequence.
[0035] The alkaline solution is a 5.5wt.% NaOH aqueous solution, the alkaline washing time is 10 minutes, the alkaline washing temperature is 30°C, and the alkaline washing method is immersion.
[0036] The acid solution is a 30 vol.% nitric acid aqueous solution, the pickling activation time is 30 s, the pickling activation temperature is 30° C., and the pickling activation method is immersion.
[0037] The washing method is flushing and the time is 2 minutes.
[0038] The main difference between Example 1 and Comparative Example 1 is whether glycolic acid is added to the anodizing solution. The physicochemical properties of Example 1 and Comparative Example 1 are now tested.
[0039] The Lab values of the anodized film of Comparative Example 1 are 48.0, 2.0 and 13.9 respectively, the corresponding roughness Ra value is 0.253±0.041μm, the thickness is 56.32±0.21μm, and the hardness is HV 0.5 The average wear rate is 2.67*10 - 5 mm 3 N -1 m -1 , average insulation resistance 194.96 MΩ.
[0040] In comparison, the Lab values of the anodized film of Example 1 are 25.9, 3.5 and 9.3, respectively, the corresponding roughness Ra value is 0.293±0.051 μm, the thickness is 54.39±0.24 μm, and the hardness is HV 0.5 The average wear rate is 279.65±8.47HV and 0.291*10-5 mm 3 N -1 m -1 , average insulation resistance 216.53MΩ.
[0041] Regarding color, the color of the film layer is evaluated by three values: L, a, and b. L represents the brightness of the object, with a value range of 0-100, indicating from black to white, and the brightness increases as the value increases; a represents the red and green color of the object, with a value range of -128-+128, positive values represent red, and negative values represent green. As the value increases, the color changes from dark green to bright pink; b represents the yellow-blue color of the object, with a value range of -128-+128, positive values represent yellow, and negative values represent blue. As the value increases, the color changes from bright blue to yellow. Compared with Comparative Example 1, both the L value and the b value of Example 1 decrease, that is, adding glycolic acid to the electrolyte will cause the color of the anodized film to change from yellow to black, and the transmittance decreases.
[0042] There is no substantial difference in terms of roughness or thickness, i.e. glycolic acid has limited effect on the roughness or thickness of anodized aluminum.
[0043] When glycolic acid is added, the hardness and wear rate of the anodized film are significantly improved, especially the wear rate is increased by an order of magnitude, that is, glycolic acid can reduce the porosity of the anodized film to a certain extent, thereby increasing the hardness, significantly improving the wear resistance, and increasing the wear rate by an order of magnitude. During the test, it was found that glycolic acid had no significant difference in the hardness stability of the anodized films of Comparative Example 1 and Example 1. The hardness fluctuation range of the two was similar, approximately within the range of ±10HV, but it was found that the stability of the wear rate was significantly affected. Specifically, the wear rate stability test was conducted on 75 samples, see Appendix Figure 1 The volatility of comparative example 1 is higher, while the data of embodiment 1 is relatively stable as a whole. The data dispersion of comparative example 1 and embodiment 1 is calculated, and it is found that the standard deviation of comparative example 1 is 4.74 times that of embodiment 1, that is, ethanolic acid has a significant improvement effect on the wear resistance stability of the anodized film.
[0044] In addition, the average insulation resistance data was statistically analyzed and the positive effect of glycolic acid on insulation stability was also found. Figure 2 The average insulation resistance of comparative example 1 is 194.96 MΩ, and the standard deviation is 14.171, while the average insulation resistance of example 2 is 216.53 MΩ, and the standard deviation is 2.709. It can be seen that glycolic acid has a significant improvement effect on the insulation stability of the anodized film.
[0045] It should be pointed out that the present invention is not limited to the above-mentioned implementation modes, and any simple modifications, equivalent changes and modifications made to the above-mentioned embodiments by any technician familiar with the profession based on the technical solution of the present invention fall within the protection scope of the present invention.
Claims
1. An aluminum alloy anodizing process, characterized in that The steps include: (1) Using aluminum alloy as the substrate, the surface of the substrate is polished with sandpaper and then soaked in an alkaline solution; (2) Wash with water, dry with cold air, and activate with acid solution; (3) Wash with water and blow dry with cold air; (4) Anodizing treatment; (5) Hydration and sealing treatment; (6) Wash with water and blow dry with cold air; The solution used in the anodizing treatment is composed of 20-40 g / L oxalic acid, 4-6 g / L glycolic acid and deionized water; The power supply for anodizing is a DC power supply, and the aluminum alloy is immersed in the anodizing solution as the anode, the voltage is 40-50V, and the temperature is 5-10℃; The hydration sealing is to seal the holes in water or water vapor at 98-105°C for 2-3 hours.
2. The aluminum alloy anodizing process according to claim 1, characterized in that Sandpaper polishing uses 400#, 600#, 800#, 1000#, 1200#, and 1500# SiC sandpaper in sequence.
3. The aluminum alloy anodizing process according to claim 1, characterized in that The alkaline solution is a 4.5-5.5wt.% NaOH aqueous solution, the alkaline washing time is 8-10min, the alkaline washing temperature is 25-30°C, and the alkaline washing method is immersion.
4. The aluminum alloy anodizing process according to claim 1, characterized in that The acid solution is a 30 vol.% nitric acid aqueous solution, the pickling activation time is 20-30s, the pickling activation temperature is 25-30°C, and the pickling activation method is immersion.
5. The aluminum alloy anodizing process according to claim 1, characterized in that The water washing method is flushing, and the time is 1.5-2 minutes.
Citation Information
Cited By
Tool clamp for cutting oxidized workpiece and cutting method
CN121989065A